Third European Workshop on Optical Fibre Sensors 2007
DOI: 10.1117/12.738575
|View full text |Cite
|
Sign up to set email alerts
|

One centimeter spatial resolution temperature measurements in a nuclear reactor using Rayleigh scatter in optical fiber

Abstract: We present the use of swept wavelength interferometry for distributed fiber-optic temperature measurements in a Nuclear Reactor. The sensors consisted of 2 m segments of commercially available, single mode optical fibers. The interrogation technique is based on measuring the spectral shift of the intrinsic Rayleigh backscatter signal along the optical fiber and converting the spectral shift to temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 7 publications
0
27
0
1
Order By: Relevance
“…Radiation darkening in silica glasses, and particularly those doped with Germanium, is most strongly observed in the UV and visible range Spencer et al 1994). Studies using COTS optical fiber have been demonstrated in vessel temperature measurements, at near infrared wavelengths where negligible photodarkening (Sang et al 2008). …”
Section: Silica Radiation Darkeningmentioning
confidence: 99%
“…Radiation darkening in silica glasses, and particularly those doped with Germanium, is most strongly observed in the UV and visible range Spencer et al 1994). Studies using COTS optical fiber have been demonstrated in vessel temperature measurements, at near infrared wavelengths where negligible photodarkening (Sang et al 2008). …”
Section: Silica Radiation Darkeningmentioning
confidence: 99%
“…Figure 2a shows the temperature profile of a piece of electrically heated fiber from OFDR Rayleigh measurements without the gas flow with various input electrical heating power. Effective temperature response coefficient of −0.67GHz/°C [13] is used for the 20-µm thick copper-alloy coated fiber to correlate the measured Rayleigh spectral shifts with distributed temperature changes. The non-uniform temperature profile can be attributed to the coating imperfection.…”
Section: Sensing Principle and Experimental Setupmentioning
confidence: 99%
“…The OFDR scheme utilizes a sweep-wavelength interferometry to spatially resolve the measurement location, this requires an elastic process such as Rayleigh scattering to ensure the optical coherence. Recently, integration of in-fiber Rayleigh backscattering measurements with OFDR technology were reported by M. Froggatt, et al, and has been employed for a variety of applications including fiber diagnosis [11] and distributed sensing of multiple parameters such as temperature [12,13], strain [12,14,15], and pressure [16].…”
Section: Introductionmentioning
confidence: 99%
“…It is based on the optical frequency domain reflectometry (OFDR) measurement of in-fiber Rayleigh scattering. This technology has been applied to provide a distributed sensing solution for in-fiber temperature, axial strain, pressure, gas flows, and hydrogen gas detection [12][13][14][15][16][17]. In this paper, both electrically and optically heated optical fibers are used to extend its application for liquid level sensing for both the room temperature and cryogenic environments down to 4 K. Distinct heating response of liquid is discriminated from gas to measure the liquid level with millimeter spatial resolution.…”
Section: Introductionmentioning
confidence: 99%